What needs to change to increase chlamydia screening in general practice in Australia? The views of general practitioners - Fairley Christopher K; Pavlin Natasha; Parker Rhian M; Hocking Jane S; Gunn Jane M (BMC, 2008)
Abstract Background Australia is considering implementing a chlamydia screening program in general practice. The views of general practitioners (GPs) are necessary to inform the design of the program. This paper aimed to investigate Australian GPs' views on how chlamydia screening could work in the Australian context. Methods This project used both qualitative interviews and a quantitative questionnaire. GPs were randomly selected from a national database of medical practitioners for both the qualitative and quantitative components. Semi-structured interviews were conducted with GPs and a thematic analysis conducted. The results of the interviews were used to design a quantitative postal questionnaire for completion by a larger sample of GPs. Up to three reminders were sent to non-responders. Results Twenty one GPs completed an interview and 255 completed the postal questionnaire. The results of the postal survey were in strong concordance with those of the interview. GPs identified a number of barriers to increased screening including lack of time, knowledge of GPs and the public about chlamydia, patient embarrassment and support for partner notification. GPs felt strongly that screening would be easier if there was a national program and if the public and GPs had a greater knowledge about chlamydia. Incentive payments and mechanisms for recall and reminders would facilitate screening. Greater support for contact tracing would be important if screening is to increase. Conclusion Chlamydia screening in general practice is acceptable to Australian GPs. If screening is to succeed, policy makers must consider the facilitators identified by GPs.